Talking about a nanny nation: investigating the rhetoric framing public health debates in Australian news media - Josephine Y Chau; James Kite; Rimante Ronto; Alexandra Bhatti; Catriona Bonfiglioli (Sax Institute, 2019)
Objectives and importance of study: News media portrayal of public health issues influences public opinion, policy action and decision making. This study aimed to analyse the use of 'nanny state' frames in Australian news media coverage; identify the stakeholders invoking this frame; determine which public health-related policies attract such framing; and investigate whether 'nanny state' framing is directly challenged in news coverage. Study type: A qualitative framing analysis. Methods: Articles featuring the term 'nanny state' that were published in Australian print newspapers during matched periods between March and September in 2017 and 2018 were sourced through Factiva, coded and analysed for content and 'nanny state' framing. Content analysis was used to identify any public health-related issues that the terminology nanny state was applied to, and who was portrayed as imposing the nanny state. Frame analysis was used to analyse what meanings are co-presented with the phrase nanny state. Results: Out of 81 print newspaper articles that included the term 'nanny state', 19% linked the term to restricting personal choice or creating dissatisfaction with too many health-related rules and regulations broadly, across a range of issues, including: bike helmets, e-cigarettes, firearm restrictions, seatbelts, pool fences and smoking bans. The next most frequent links were to regulations on alcohol (17%), road safety (14%), obesity-related issues (7%) and tobacco control (6%). Of the 81 articles, 53% appeared in news publications owned by News Corporation Australia, 20% in Fairfax Media (Nine Entertainment) publications, 17% in Daily Mail and General Trust and 10% in publications owned by other organisations. Governments were the entity most frequently framed as imposing the nanny state. Most nanny state framings (73%) were negative towards public health controls and focused on policies and regulations. Nanny state was portrayed as an assault on freedom and choice (14%) and used to attack proponents of nanny state controls (11%), while few articles framed the nanny state (7%) in a favourable light. Conclusions: 'Nanny state' is a rhetorical device commonly used in Australian news media that may contribute to discrediting of the regulation of a range of health-related issues. News Corp publications are a major propagator of nanny state rhetoric in Australian newspaper media. Public health advocates are not commonly represented within nanny state debates within the news media.